PENILAIAN RESIKO KONTAMINASI LOGAM BERAT DI LAHAN SAWAH DAN TANAMAN PADI DI DAS BRANTAS, KABUPATEN JOMBANG - Cicik Oktasari Handayani; Sukarjo Sukarjo; Anik Hidayah (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Risk assessment of heavy metal contamination is carried out on Pb, Cd, Fe, Cr, Cu, Co, Mn, and Zn metals in four wetland zoning areas in Jombang Regency and determining potential non-carcinogenic and carcinogenic risks to the community. The soil and rice samples from the four rice field zones were destructed by wet ashing method and measured by AAS. The concentration of heavy metals in the soil is Fe> Mn> Zn> Cu> Pb> Co> Cr> Cd. The concentration of heavy metals in the rice is Fe> Mn> Zn> Cu> Cr> Co> Pb> Cd. The ability to transfer heavy metals from soil is to rice Zn> Mn> Cr> Co> Pb> Fe> Cu> Cd, respectively. The daily intake of each heavy metal through rice consumption is Pb (0.003), Cd (0), Fe (0,165), Cr (0.011), Cu (0.013), Co (0.008), Mn (0.072), and Zn (0.074) in mg / (kg.day). Hazard Quotient Pb value is greater than 1, while CR (Cancer Risk) for Cr is greater than 10-4. The potential for total non-carcinogenic risk ranged from 1.82 to 3.79, while the potential carcinogenic risk ranged from 4,5.10-3-6,4.10-3. Long term exposure to heavy metals through rice consumption may pose a potential carcinogenic and carcinogenic health risk to local people.Â